Power, Corruption, and Class Struggle: John Arden’s the Workhouse Donkey as a Political Examination of Local Government and Social Conflict in Post-War - Sibgatulah Nazki PhD Scholar; Imtiyaz Ahmad Bhat (MultiTech Publisher, 2024)
This study examines John Arden’s play The Workhouse Donkey as a political drama. The purpose is to explore how the play exposes power struggles, corruption, and class conflict within local government. The research shows how Arden uses theatre to critique political systems. It highlights how the play raises social awareness about post-war Britain’s urban and social problems. First performed in 1963, The Workhouse Donkey reflects the political tensions of post-war Britain. Local councils faced criticism over urban redevelopment, housing shortages, and working-class displacement. Arden’s play presents a fictional town council. Personal ambition, greed, and rivalry lead to social decay. Arden reveals how bureaucracy and self-interest destroy public welfare. The play belongs to 1960s political theatre, which questioned authority and exposed social inequality. This research uses a qualitative approach. It focuses on close reading of The Workhouse Donkey. The study examines dialogue, characters, plot, and staging to find political themes. It also uses Arden’s essays and critical responses to explain the play’s context. The research applies political theatre theory and class analysis to understand Arden’s methods. The study finds that The Workhouse Donkey shows local government as a symbol of class struggle. Arden presents a system ruled by profit, competition, and survival. Political decisions ignore the social good. Through realistic dialogue and complex characters, the play exposes how corruption becomes normal. It shows how the working class is excluded from decisions that affect them. The analysis shows that Arden turns a council meeting into political conflict. His picture of council life reflects wider social divisions. The play’s structure, with fast dialogue and shifting alliances, shows the confusion of a broken system. The research proves that The Workhouse Donkey is more than local satire. It is a commentary on post-war Britain’s battles with power, urban change, and social justice. This study finds that The Workhouse Donkey is a strong example of political theatre. Arden uses local government to expose class conflict and system failure. The play is still relevant today. It reflects debates about political responsibility, corruption, and inequality. Arden shows how political systems protect the powerful. The weak are ignored. His play remains an urgent call for awareness and change